Code stroke in an emergency department - evaluation of results after 7 years of protocol implementation - Barreira, Ilda (2018)
Fibrinolysis reduces mortality and disability after an ischemic stroke, and its benefits are documented with level of evidence I [1]. The major goal of the Code Stroke (CS) is to treat the eligible cases by fibrinolysis, within the therapeutic window of 4.5 hours after symptom onset [2]. Thus, an emergency department must operate efficient mechanisms to receive, diagnose, treat or transfer patients with stroke [3]. Objective: The main objective was to evaluate the results of the CS protocol implementation in an Emergency Department (ED) of a hospital in the North of Portugal. As secondary objectives we aimed to: (i) Characterize the patients in sociodemographic and clinical variables; (ii) Calculate the activation rate of CS protocol and the rate of fibrinolysis. Methods: Retrospective descriptive analysis, using data from the Manchester triage system and other secondary source of information, of all patients with ischemic stroke, hemorrhagic stroke, and transient ischemic attack (TIA) admitted to the Emergency Department between January 1, 2010 and December 31, 2016. Socio-demographic data, care times, cardiovascular risk factors and other clinical variables were collected. The statistical analysis was performed by ANOVA, at 0.05 significance level. Results: In the 7 years analyzed, 1200 patients with cerebrovascular disease were admitted in the ED. Among this patients, 63.0% presented ischemic stroke, 17.3% hemorrhagic stroke and 19.8% TIA. The population was predominantly male (54.8%) and had a mean age of 77.4 (± 11.2) years. Stroke code was activated 431 times, covering 37.2% (n= 282) of ischemic stroke, and have received thrombolytic therapy 18.4% (n= 52) of these patients. Door-to-needle time was, in average, 69.5 minutes. Mean (±SD) NIHSS (National Institutes of Health Stroke Scale) score was 14.8 (±5.2) before treatment, decreasing to 11.8 (± 6.0) at two hours post- fibrinolysis (p <0.05). For all patients (N= 1200), we obtained the following prevalences of risk factors: Hypertension (64.7%), dyslipidemia (30.3%), diabetes (26.5%), atrial fibrillation 23.3%), obesity (12.9%), smoking (6.3%) and ischemic heart disease (5.9%). The 24-hour mortality rate was 0.9% for ischemic stroke, 10.6% for hemorrhagic stroke, and 0% for TIA. Conclusions: High rates of activation protocol were obtained for acute ischemic stroke, but only 52 patients met the criteria for fibrinolysis. The high age and comorbidity of patients with ischemic disease and its origin, predominantly rural, may have influenced the therapeutic window and the eligibility criteria for fibrinolysis.